Code Switching and Mixing in Education: Strategies for Effective Language Learning Class - Nugraeni, Oktavia; Salwa Nabilla; Rahma Kamila (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2025)
Language is very important for communicating in the modern globalized world. Speakers who speak more than one language are called code-mixers. This study looked at how effective code-switching and blending are in English classes outside of English departments. This research collects data through observations and notes of students in English classes that use full English and use code switching and mixing. In addition, data about student understanding was collected through questionnaires. The results of this research will provide insight into how effective code-switching and mixing are in the language learning classroom. In addition, this research aims to provide valuable implications for language educators and their students.